The measurement of farmers' risk attitudes using a non-structural approach - Kim, Tae-Hun (농촌경제, 31(2), 2008)
This study estimates farmers' risk attitudes in Missouri using a non-structural approach over time. The non-structural approach proposed by Antle (1989) allows for multiple outputs and various types of risk faced by farmers and doesn't require specific functional forms for utility or production. This approach can also provide farmers' risk attitudes over time. The results show that farmers' risk attitudes are risk loving and change over time, while farmers' risk attitude is generally assumed to be risk averse and very stable over time. Since this approach has the different definition of risk attitude, the results of this study may be a bit different from previous studies.